Muscle proteome of crossbred cattle that received vitamin A at birth: impacts on meat quality traits - Scapol, Rayssa S. [UNESP]; Baldassini, Welder A. [UNESP]; Gagaoua, Mohammed; Ramírez-Zamudio, Germán D.; Ladeira, Márcio M.; Poleti, Mirele D.; Ferraz, José Bento S.; Torres, Rodrigo de N.S. [UNESP]; Torrecilhas, Juliana A. [UNESP]; Pereira, Guilherme L. [UNESP]; Machado-Neto, Otavio R. [UNESP]; Curi, Rogério A. [UNESP]; et al. (Elsevier, 2023)
This study aimed to evaluate the skeletal muscle proteome of calves that received an intramuscular application of vitamin A at birth and its impacts on meat quality. Forty male crossbred calves were used from birth to feedlot finishing. On the day of birth, 20 calves were injected intramuscularly with a single dose of 300,000 IU of vitamin A and the other 20 animals received placebo (control). After weaning at 210 days, the animals of the two treatments were feedlot finished for 180 days. Longissimus muscle samples were collected for proteome analysis and meat quality assessment. There was a trend (P = 0.07) towards more tender meat in animals that received vitamin A compared to control (WBSF = 3.92 ± 0.16 kg vs. 4.23 ± 0.15). Meat color, pH and cooking loss were not affected (P > 0.05). Vitamin A treatment resulted in a more than 50% increase in intramuscular fat (IMF) content (P < 0.05) compared to control (4.10 ± 0.35% vs. 2.57 ± 0.27%). The intramuscular injection of vitamin A affected the post-mortem muscle proteome and the protein-protein interactions. A greater abundance of proteins involved in three main pathways were observed these being energy metabolism (GAPDH, ENO3, TPI1, CKM, and COX5A), muscle contraction (ACTB, ACTC1, ACTG1, ACTG2, ACTA1, ACTA2, ACTN1, ACTN2, ACTN3, TPM1, TPM2, TPM3, MYH1, PDLIM3, and TNNT3), protein binding, transport, and signaling (TUBA4A, VIM, TBA1B, and EEF1A2). A greater abundance of oxidative stress and cellular defense proteins (HSPA8 and DNAJC18) was specifically observed in the control treatment. Vitamin A upregulated key biological processes related to energy metabolism, which favored IMF accumulation during the finishing phase.
Keywords: Adipogenesis; Biochemical processes; Bos indicus; Feedlot; Lipogenesis; Muscle proteome; Retinoic acid